The effects of dexmedetomidine on cerebral glucose metabolism, systemic cytokine release and cerebral autoregulation: Studies on healthy volunteers and aneurysmal subarachnoid haemorrhage patients - Kallioinen, Minna (fi=Turun yliopisto|en=University of Turku|, 2022)
Dexmedetomidine is a very selective α2-agonist that has become a popular sedative in the intensive care unit. It has characteristics that make it appealing especially for neurologically compromised patients. Aneurysmal subarachnoid haemorrhage (aSAH) is a complicated disease where cerebral physiology and the regulation of cerebral blood flow, i.e., autoregulation, are often disturbed. It is important that the used anaesthetic and sedative drugs do not cause further damage. The aim of this study was to explore how dexmedetomidine affects cerebral glucose metabolism, systemic cytokine response, and cerebral autoregulation. The first two studies included healthy male volunteers. The first study investigated the effects of dexmedetomidine on cerebral glucose metabolism along with three other anaesthetic drugs (propofol, sevoflurane, S-ketamine) and a placebo group. The second study investigated the effects of dexmedetomidine and propofol on the release of cytokines, chemokines, and growth factors. The third study included 10 aSAH patients. We examined the effects of dexmedetomidine on cerebral autoregulation with three increasing doses after the baseline sedation with propofol and/or midazolam was suspended. In the volunteer studies, we found that the cerebral glucose metabolism was lowest with dexmedetomidine. In addition, we found that dexmedetomidine induced an anti-inflammatory cytokine response, whereas propofol induced a partly pro-inflammatory and slightly anti-inflammatory cytokine response. In aSAH patients, dexmedetomidine did not alter the static cerebral autoregulation compared to baseline. However, after the dose of 1.0 µg/kg/h, we observed a minor but statistically significant decrease in dynamic cerebral autoregulation which may suggest that in aSAH patients sedated with dexmedetomidine, sudden decreases in mean arterial pressure should be avoided.